2008
DOI: 10.1016/j.str.2007.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Structure and DNA Binding of the Human Rtf1 Plus3 Domain

Abstract: The yeast Paf1 complex consists of Paf1, Rtf1, Cdc73, Ctr9, and Leo1 and regulates histone H2B ubiquitination, histone H3 methylation, RNA polymerase II carboxy-terminal domain (CTD) Ser2 phosphorylation, and RNA 3' end processing. We provide structural insight into the Paf1 complex with the NMR structure of the conserved and functionally important Plus3 domain of human Rtf1. A predominantly beta-stranded subdomain displays structural similarity to Dicer/Argonaute PAZ domains and to Tudor domains. We further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 50 publications
6
68
0
1
Order By: Relevance
“…We conclude that, because of the absence of these interactions, the localization of the HMD is deregulated and its histone modification function appears to be uncoupled from RNA pol II. Most likely, other regions of Paf1C, such as the Rtf1 ORF association/Plus3 domain (44,48), are dominant to the HMD in controlling the localization of Paf1C. Based on our analysis of paf1Δ, ctr9Δ, and cdc73Δ mutants, Rtf1 is the key member of Paf1C with respect to the establishment of H2B K123 ubiquitylation and downstream marks.…”
Section: Discussionmentioning
confidence: 89%
“…We conclude that, because of the absence of these interactions, the localization of the HMD is deregulated and its histone modification function appears to be uncoupled from RNA pol II. Most likely, other regions of Paf1C, such as the Rtf1 ORF association/Plus3 domain (44,48), are dominant to the HMD in controlling the localization of Paf1C. Based on our analysis of paf1Δ, ctr9Δ, and cdc73Δ mutants, Rtf1 is the key member of Paf1C with respect to the establishment of H2B K123 ubiquitylation and downstream marks.…”
Section: Discussionmentioning
confidence: 89%
“…The PLUS3 domain is thought to play a role in nucleic acid binding through 3 conserved positive amino acids (19). There are 5 proteins in Arabidopsis with the PLUS3 domain (Fig.…”
Section: Tzp Is a Large Nuclear-localized Protein Encoded By A Singlmentioning
confidence: 99%
“…Three of these also have a SWIB domain, two have either a CCCH or a C3H3C4 zinc finger, and VERNALIZATION INDEPENDENT 5 (VIP5) contains only the PLUS3 domain (20). VIP5 is a homolog of the yeast RTF1 protein, which is part of the yeast Paf1 complex that regulates histone H2B ubiquitination, histone H3 methylation, RNA polymerase II carboxy-terminal Ser-2 phosphorylation, and RNA 3Ј end processing (19). The SWIB domain-containing proteins are part of the SWI/SNF chromatin-remodeling complex (21).…”
Section: Tzp Is a Large Nuclear-localized Protein Encoded By A Singlmentioning
confidence: 99%
“…Deletion of either of these subunits reduces the levels of Paf1C that immunoprecipitate with RNA pol II or localize to transcribed genes (10,13). Mutational studies have identified the Plus-3 domain of Rtf1 as being required for Paf1C occupancy on active genes (16), and interestingly, biochemical experiments have revealed binding of the Rtf1 Plus-3 domain to DNA substrates that mimic the transcription bubble (40).…”
mentioning
confidence: 99%